Defend and Befriend : The U.S. Marine Corps and Combined Action Platoons in Vietnam - Southard, John, 1980- (Book collections on Project MUSE., 2014)
After relatively successful military interventions in Iraq in 1992 and Yugoslavia in 1998, many American strategists believed that airpower and remote technology were the future of U.S. military action. But America's most recent wars in the Middle East have reinforced the importance of counterinsurgency, with its imperative to ""win hearts and minds"" on the ground in foreign lands. In both Iraq and Afghanistan, the U.S. military has studied and experimented with the combined action platoon (CAP) concept used from 1965 to 1971 by the Marine Corps in Vietnam. Consisting of twelve Marines, a medi.